Artificial Neural Networks In The Prediction Of Atheroma Plaque Vulnerability - Caballero Masa, Ricardo; Martínez Barca, Miguel Ángel; Peña, Estefanía (Jornada de Jóvenes Investigadores del I3A, 2022)
The prediction of the vulnerability of atheroma plaque by means of neural networks allows a rapid response to be given for a specific patient in clinical practice. To perform this prediction, an artificial neural network (ANN) has been developed takes as input data the deformations of the atherosclerotic coronary artery and gives as a result the mechanical properties of the atherosclerotic coronary artery. These have been used to determine the stresses in the fibrotic layer and, ultimately, whether or not the plaque is vulnerable.